Dataset for 'Standoff measurement of ageing-related carbonyl bonding in bitumen. Part 1: Measurement strategy and instrument design principles' - Hodgkinson, Jane; Davis, Nicholas; Tatam, Ralph P. (Cranfield University, 2024)
We describe a strategy to make in-situ measurements of a spectroscopic marker of ageing in bitumen binders used on asphalt-paved roads. Oxidation of bitumen at the surface increases the number of carbonyl (C=O) bonds, and this can be measured in the 6μm region (1700cm-1) of the mid-infrared. We propose a measurement strategy to make standoff measurements of surface reflectivity in this region, despite the challenge presented by numerous strong absorption lines from atmospheric water vapour within the optical path. We describe an instrument design making measurements at 4 discrete laser wavelengths, namely 1593.0, 1641.4 and 1731.3 cm-1 (around 6µm) and at 2633.6 cm‑1 (3.8µm), the first 3 responding to carbonyl absorption and the fourth acting as a spectral reference that is substantially unaffected by ageing. Part 2 of this paper describes the implementation of such an instrument and its experimental performance
Keywords: bitumen; asphalt; mid-IR spectroscopy; ageing; reflectivity